2014
DOI: 10.1148/radiol.14140295
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Characteristics of Contralateral Asymptomatic Patellofemoral Joints in Patients with Unilateral Instability

Abstract: ).q RSNA, 2014 Purpose:To test the hypothesis that in patients with unilateral patellofemoral instability (PI), the contralateral asymptomatic joints have abnormal morphology and imaging features of osteoarthritis (OA) at four-dimensional (4D) computed tomography (CT). Materials and Methods:The institutional review board approved this HIPAA-compliant retrospective study. Informed consent was waived. Radiology records were reviewed to identify 25 patients (male-female ratio, 0.56; median age, 20 years; range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 35 publications
1
24
0
1
Order By: Relevance
“…The most common height abnormalities are patella alta and baja. 1,2 Patella alta refers to a highriding patella, which can be associated with lateral patellar subluxation and tilt, as the elongated patellar tendon allows increased mediolateral translational mobility and axial rotation of patella due to suboptimal engagement in the apex of trochlear sulcus. It also predisposes to chondromalacia patellae, stripping of patella along its anterior surface (enthesopathy) and patellar tendon rupture.…”
Section: Trochlear Depth >3-5 MMmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common height abnormalities are patella alta and baja. 1,2 Patella alta refers to a highriding patella, which can be associated with lateral patellar subluxation and tilt, as the elongated patellar tendon allows increased mediolateral translational mobility and axial rotation of patella due to suboptimal engagement in the apex of trochlear sulcus. It also predisposes to chondromalacia patellae, stripping of patella along its anterior surface (enthesopathy) and patellar tendon rupture.…”
Section: Trochlear Depth >3-5 MMmentioning
confidence: 99%
“…1 PFPS is a challenging diagnosis for clinicians and radiologists alike, and many differential considerations exist. Radiographic, CT and MRI evaluations are commonly employed to further elucidate the PFPS-related lesions 2,3 and exclude other related differential diagnoses, such as lateral meniscus tear, extensor tendon tear, anterior tenosynovial giant cell tumour and plica syndrome. This article comprehensively discusses the role of many static and dynamic stabilizers involved in the biomechanics of the PF joint, findings on conventional radiography and cross-sectional imaging that aids in the diagnosis and characterization of PFPS, and current perspectives of various management (conservative and surgical) approaches.…”
mentioning
confidence: 99%
“…CT scans allow for 3-dimensional reconstruction, and dynamic (4-dimensional) imaging is available at some centers. 8 MRI is widely available and has the advantage of no radiation exposure to patients. Camp et al 9 found that the TT-TG distance had excellent inter-rater reliability on MRI and CT but that measurements were an average of 3.8 mm greater on CT compared with MRI.…”
Section: See Related Article On Page 2026mentioning
confidence: 99%
“…İskelet sisteminin temel görüntüleme yöntemi olan direkt grafi (DG) ve bilgisayarlı tomografi (BT) gibi yön-temler kıkırdak patolojilerini belirleyebilmek için yetersizdir. Diğer taraftan, Manyetik rezonans görüntüleme (MRG) ile kemik ve çevre yumuşak dokulara ek olarak kıkırdak doku hakkında bilgi edinilebilir (2,3) . Artroskopi ile hem tanı konulabilir hem de tedavi uygulanabilir.…”
Section: Introductionunclassified